Variabilidade da frequência cardíaca em cães com degeneração mixomatosa crônica da valva mitral - Navarrete Ampuero, Roberto Andrés [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Study of heart rate variability in the time domain, performed in 48 dogs of different breeds of small to medium sized, with chronic myxomatous degeneration of the mitral valve, aged in heart failure classes (CHF) proposed by ISACHC. The animals showed clinical signs of: cough, fatigue, dyspnea group class 2, in order of prevalence. Electrocardiographic examination in dogs lose respiratory sinus arrhythmia, going to sinus rhythm, with display: increase in p wave duration and amplitude, QRS duration and in R wave amplitude when developing this valvular disease and increase class. Dogs with MMVD in stages of ICC moderate (class 2) compared with early stages (class 1a and class 1b) of the disease had higher echocardiographic values: Relations LA/Ao, DIVEd/Ao, DIVEs/Ao, ESIVs/Ao, EPPVEd/Ao, EPPVEs/Ao, FE%,FEC%, PVE e PVA mitral. The present study showed that heart failure in dogs with MMVD, had decreased values of NN medium (NNM), SDNN, SDNNindex and pNN50%. Implying a decrease in the participation of the parasympathetic nervous system and an increase in the participation of the sympathetic nervous system. Furthermore, we observed an increase in mean HR and increased QRS complexes (NQRS) which are also indicators of increased participation of the sympathetic system. We determined the prevalence of ventricular arrhythmias in the three groups, with a similar proportion of supraventricular arrhythmias in the clinical group. Both ventricular arrhythmias and supraventricular arrhythmias were isolated character in the pre-clinical and complex character in the clinical group. Especially supraventricular arrhythmias and ventricular arrhythmias may manifest themselves throughout the progression of the disease, initial ventricular arrhythmias, with further increase supraventricular arrhythmias as a consequence of atrial dilation. The correlations obtained in Holter examination were, positive correlation ...

Estudo da variabilidade da frequência cardíaca, no domínio do tempo, realizado em 48 cães de diferentes raças de pequeno a médio porte, com degeneração mixomatosa crônica da valva mitral, estadiados em classes de insuficiência cardíaca congestiva (ICC) proposta pela ISACHC. Os animais apresentaram sinais clínicos de: tosse, cansaço, dispneia no grupo classe 2, em ordem de prevalência. No exame eletrocardiográfico os cães perdem arritmia sinusal respiratória, passando para ritmo sinusal, junto podem apresentar: aumento da onda P em duração e amplitude, complexo QRS em duração e amplitude da onda R quando desenvolvem esta doença valvular e aumentam de classe. Os cães com DMVM em estádios de ICC moderados (classe 2) em comparação com estágios iniciais (classe 1a e classe 1b) da doença apresentaram maiores valores ecocardiográficos: relação AE/Ao, DIVEd/Ao, DIVEs/Ao, ESIVs/Ao, EPPVEd/Ao, EPPVEs/Ao, FE%,FEC%, PVE e PVA mitral. O presente estudo mostrou que a insuficiência cardíaca em cães com DMVM, tinha diminuído os valores de NN médio (NNm), SDNN, SDNNindex e pNN50%. Inferindo uma diminuição da participação do sistema nervoso parassimpático e um aumento da participação do sistema nervoso simpático. Além disso, foi observado um aumento da FC média e aumento número de complexos QRS (NQRS) que também são indicadores de maior participação do sistema simpático. Determinou-se um predomínio das arritmias ventriculares nos três grupos, com semelhante proporção das arritmias supraventricular no grupo clínico. As arritmias tanto ventriculares como as arritmias supraventriculares foram de caráter isolado nos grupos pré-clínicos e de caráter complexo no grupo clínico. As correlações obtidas no exame Holter foram correlação positiva entre: NNm v/s NQRS na classe 2, classe 1b e classe 1a (r= 0,978, r= 0,932, r= 0,962); NNm v/s pNN50% na classe 2 e classe ...
Keywords: Cão; Degeneração (Patologia); Arritmia; Variabilidade do batimento cardíaco; Valvula mitral - Doenças; Degeneration (Pathology)